2014
DOI: 10.1371/journal.pone.0095880
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of GFP-Positive Hepatocytes Transplanted into the Liver of Syngeneic Wild-Type Rats Pretreated with Retrorsine

Abstract: Background and AimGreen fluorescent protein (GFP) is a widely used molecular tag to trace transplanted cells in rodent liver injury models. The differing results from various previously reported studies using GFP could be attributed to the immunogenicity of GFP.MethodsHepatocytes were obtained from GFP-expressing transgenic (Tg) Lewis rats and were transplanted into the livers of wild-type Lewis rats after they had undergone a partial hepatectomy. The proliferation of endogenous hepatocytes in recipient rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…More importantly, the transplanted hepatocytes were still visible at day 28, which was chosen for evaluation of hepatocyte engraftment in the present study. Interestingly, Maeda et al recently published results regarding the fate of GFP‐expressing hepatocytes transplanted in the liver of syngeneic wild‐type rats after retrorsine administration . Transplanted hepatocytes were still visible at day 28, but the authors demonstrated the disappearance of GFP‐expressing hepatocytes at day 42, most likely involving an immunological reaction against GFP.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the transplanted hepatocytes were still visible at day 28, which was chosen for evaluation of hepatocyte engraftment in the present study. Interestingly, Maeda et al recently published results regarding the fate of GFP‐expressing hepatocytes transplanted in the liver of syngeneic wild‐type rats after retrorsine administration . Transplanted hepatocytes were still visible at day 28, but the authors demonstrated the disappearance of GFP‐expressing hepatocytes at day 42, most likely involving an immunological reaction against GFP.…”
Section: Discussionmentioning
confidence: 99%
“…Implying an underlying damaging process, GFP-positive hepatocytes in wild-type rats livers decreased more rapidly than the wild-type hepatocytes transplanted into the GFP transgenic rat livers. Moreover, GFP-positive hepatocytes attracted CD4+ and CD8+ infiltrating inflammatory cells, which is consistent with an immunological response [ 7 ]. Additionally, immunologic modification by bone marrow transplantation and administration of Tacrolimus, a T-cell inhibitor agent, showed increased survival of transplanted GFP-positive hepatocytes.…”
Section: Immunogenicity Of Gfp (Table 1 )mentioning
confidence: 68%
“…Hepatocytes obtained from GFP transgenic rats were transplanted into the livers of wild-type rats. For comparison, wild-type hepatocytes were transplanted into GFP-transgenic rat livers as well [ 7 ]. After showing engraftment using fluorescent microscopy, the transplanted hepatocytes were tracked for 48 days.…”
Section: Immunogenicity Of Gfp (Table 1 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that long-term hepatocyte proliferation and survival requires a combination of proliferative stimuli and suppression of host hepatocytes. This is typically done using partial hepatectomy which involves a 60–80% removal of the liver, and retrorsine treatment to inhibit endogenous hepatocytes [ 37 , 39 ]. The lack of liver pre-conditioning is one of the major limitations of this study.…”
Section: Discussionmentioning
confidence: 99%